De facto seniority in the primary market for corporate bonds - Kim, Ju Hyun (Finance Research Letters, 2024)
This paper documents the existence of de facto seniority in the primary market for corporate bonds. Analysis of Korean data from 2018 to 2021 shows that investors require larger yield spreads for debt with later maturities in an issuance cohort. This relation is robust to controlling for macroeconomic conditions, important issue characteristics, the stated use of proceeds, and alternate fixed effects.
Keywords: Bond maturity; Corporate bonds; De facto seniority; Issuance spread; Primary market